Analisis Kepribadian Anak Ekstrovert Menurut Teori Carl Gustav Jung - Fadilah, Risydah; Juro, Az Zahra; Daifah, Cut; Rahmahwati, Dina (ANWARUL, 2023)
Personality is a complete set of attitudes, behaviors, thoughts, feelings and values that influence individuals to do things according to their environment. In addition, personality is often interpreted as a prominent trait in a person, for example, a person who has a friendly nature will be a person with a "friendly personality". Personality theory is a combination of teleological and causal views. Human behavior is determined not only by individual racial histories (causality), but also by individual goals and aspirations (teleology). This study aims to determine the personality side possessed by S students at MAN 1 ACEH southeast, using the personality theory according to Carl Gustav Jung.